A comparison of development‐matched and age‐matched targets on play skills of children with autism spectrum disorder. Issue 1 (22nd November 2021) - Pane, Heather M.; Sidener, Tina M.; Reeve, Sharon A.; Kisamore, April; Nirgudkar, Anjalee
Abstract : Although neurotypical children often spend the majority of their time engaged in play activities, children with autism spectrum disorder (ASD) can present with substantial delays in the development of play skills, requiring intensive intervention. Although targets for language and basic learning skills are often selected based on the development of neurotypical children (e.g., Sundberg, 2008), little research has been conducted on methods for selecting play skill targets. The current study compared acquisition of play skills that were development‐matched (DM) and age‐matched (AM) with 4 children diagnosed with ASD. Targets were selected based on the results of the Developmental Play Assessment (DPA; Lifter, 2008). No contrived prompts or consequences were used to teach play skills in either condition. Generalization was programmed for by teaching with 3 sets of toys in both conditions. All participants demonstrated acquisition of DM play targets and generalization to novel toys; none of the participants acquired AM play targets.